ChemInform Abstract: Magnetic Order and Crystal Structure Study of YNi4Si‐Type NdNi4Si. Issue 9 (March 2015) - Yao, Jinlei; Isnard, O.; Morozkin, A. V.; Ivanova, T. I.; Koshkido'ko, Yu. S.; Bogdanov, A. E.; Nikitin, S. A.; Suski, W.
Abstract NdNi4Si is prepared by arc melting of stoichiometric amounts of the elements followed by annealing under Ar (quartz tube, 1070 K, 200 h).